Peran Organisasi Remaja Masjid Dalam Membentuk Pendidikan di Masyarakat Perspektif Islam - Heri Sugiantoro; Nailud Darojaatul Aliyah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Teenagers are the successors of the future of a nation in the future. Teenagers are a benchmark for the sustainability and goodness of a nation, therefore this research aims to find out youth activities that can continue the leadership relay with the role of mosque teenagers in forming the younger generation. This paper uses library research methods, namely a series of activities related to library data collection methods. With this article, the role of mosque youth does not only focus on the field of religion, but more than that, all aspects related to education can result from their role. Their thoughts and actions are really needed by society, because in society they are defined as organizations that can build and invite society with the activities they produce to provide positive activities that can build positive education in society.